CHARACTERISTICS AND AMINO ACID PROFILE OF JELAWAT FISH MEAL (Leptobarbus hoevenii) WITH DIFFERENT COOKING METHODS - Nurmawilis Nasution; Edison '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to know the characteristics and amino acid profile of jelawat fish meal with different cooking methods three cooking of methods, they are T0 ( control), T1 (steaming) and T2 (presto). The samples then analyzed the amino acids, the characteristics of flour and proximate level. Research’s result at T0, T1, T2 has a value in a row is amino acids 58.91%, 58.64%, 59.98%; yield 11.64%, 9.19%, 9.44%; whiteness 46.92%, 57.76%, 64.07%; water absorption 73.2%, 61.2%, 56%; water content 6.42%, 8.38%, 8.70%; ash content 9.62%5.22%, 3.52%; protein content of 65.10%, 65.30%, 68.80%; fat content 14.60%, 9.45%, 5.80%. The conclusion of this research was jelawat fish meal with cooking methods presto had the most optimal amino acids and protein content.Keywords: Jelawat fish meal, cooking methods, amino acid